Physical activity and psychosomatic status in patients with Behçet's disease during coronavirus disease pandem - Bağlan Yentür, Songül; Bilek, Furkan; Koca, Süleyman Serdar (NLM (Medline), 2022)
OBJECTIVE: The aim of this study is to examine the changes in physical activity level, fatigue, depression, and sleep quality in patients with Behçet's disease during the COVID-19 pandemic. METHODS: The study was designed as an online questionnaire applied to individuals who are being followed up with the diagnosis of Behçet's disease in the rheumatology department. Data were collected using multiple scales including International Physical Activity Questionnaire (IPAQ), Fatigue Severity Scale (FSS), Beck Depression Inventory (BDI), Pittsburg Sleep Quality Index (PSQI), and Visual Analogue Scale (VAS) to evaluate physical activity level, fatigue, depression, sleep quality, and pain, respectively. RESULTS: Sixteen patients diagnosed with Behçet's disease were included in the study. No statistically significant difference was observed between the IPAQ, FSS, BDI, PSQI, and VAS assessment scores before COVID-19 and during COVID-19 period (P > .05 for all). CONCLUSION: Thinking of the negative effects of aggressive clinical symptoms, Behçet's disease patients should be supported in physical activity and psychosocial status.
Keywords: Behcet Syndrome; COVID-19; Depression; Exercise; Fatigue; Humans; Pandemics; Quality of Life; Behcet disease; complication; depression; exercise; fatigue; human; pandemic; psychology; quality of life